2019
DOI: 10.11606/issn.1981-4690.v33i1p115-126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de baixos níveis de força muscular e fatores associados em adolescentes de uma cidade do sul do Brasil

Abstract: A força muscular é necessária para realização de atividades diárias, sendo considerada marcador de saúde global. O objetivo deste estudo foi estimar a prevalência de baixos níveis de força de preensão manual (FPM) em adolescentes e verificar fatores (sociodemográficos, estilo de vida e status de peso) correlatos. A população de escolares da cidade de São José, SC, Brasil, era formada por 5.182 estudantes. Para o presente estudode base escolar e delineamento transversal, 923 adolescentes de 14 a 19 anos de idad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The references of included studies were analyzed in order to identify possible information on the theme not verified during the systematic search; however, no additional studies in relation to those previously identified were included. Thus, 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The references of included studies were analyzed in order to identify possible information on the theme not verified during the systematic search; however, no additional studies in relation to those previously identified were included. Thus, 13 studies [17][18][19][20][21][22][23][24][25][26][27][28][29] were included in this review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies with cross-sectional design were part of the present review. Of this total, seven studies were carried out in the southern region of Brazil (Santa Catarina, n = 04; Paraná, n = 03) 19,[21][22][23][24]26,27 , two studies in the southeastern region (São Paulo, n = 01; Minas Gerais, n = 01) 18,29 , two studies in the northeastern region (Alagoas, n = 01; Piauí, n = 01) 25,28 and one study in the northern region (Amazonas) 17 . Additionally, one study 20 was conducted in states included in the southern and southeastern regions of Brazil (Paraná and São Paulo, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, when it comes to adolescents, there is still no knowledge of studies dealing with this subject. As a result, studies have been restricted to using cutoff points based on adolescents from other countries 7,14 , which may not reflect the true Brazilian condition regarding muscle strength in this age period. For example, in a previous meta-analysis, it was reported that HGS values are substantially lower in individuals from middle-income countries when compared to high-income countries, possibly due to differences in body size typical of each continent 15 .…”
Section: Introductionmentioning
confidence: 99%